Insights into Food Intake, Overall Diet Quality, and Stool Short-Chain Fatty Acids during Treatment for Rectal Cancer: A Pilot Study - Gonzalez-Mercado, Velda J.; Finik, Jackie; Marrero, Luis M.; Wong, Agnes; Foley, Roberto; Aoizerat, Bradley E. (Puerto Rico Health Sciences Journal, 2025)
Objective: To describe food intake and overall diet quality during neoadjuvant concomitant chemotherapy and radiation therapy (nCRT) for rectal cancer. We also explored associations between Prime Diet Quality Score (PDQS) and short-chain fatty acid (SCFA) levels in stool at the end of nCRT in a subset of participants. Methods: Thirty-two participants provided a 24-hour dietary recall, while 18 provided stool samples for SCFA analysis. Results: The reported intake of 11 healthy food groups (e.g., dark green vegetables, fish) was low (<50% of participants) before treatment, while 4 unhealthy food groups (e.g., processed meat, sugar-sweetened beverages) were high (>50%), both before and after treatment. Higher propionate levels were associated with higher PDQS values. Conclusion: Participants reported reduced dietary intake and diet quality during nCRT. Additional study is warranted to determine whether gut metabolites may mediate the impact of low diet quality.